2004
DOI: 10.2298/mpns0406219n
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric adverse effects induced by recombinant interferon alfa in patients with chronic hepatitis C

Abstract: Interferon causes psychiatric disorders that are usually mild and reversible. They disappear either spontaneously, while patients are still receiving therapy or after temporary cessation of interferon alfa therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…However, a previous study showed that being female was a risk factor for development of depression only in the early phase of PEG-IFN-α treatment (31). Another study also showed that females had more psychiatric side effects at PEG-IFN-α (32). However, some previous studies did not find any significant relationship between gender and depression in PEG-IFN-α therapy (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study showed that being female was a risk factor for development of depression only in the early phase of PEG-IFN-α treatment (31). Another study also showed that females had more psychiatric side effects at PEG-IFN-α (32). However, some previous studies did not find any significant relationship between gender and depression in PEG-IFN-α therapy (33).…”
Section: Discussionmentioning
confidence: 99%
“…Interferon therapy for patients with CHC is associated with significant psychiatric side‐effects, such as depression . Previous studies showed that the median time required for the appearance or worsening of the depressive symptoms was 15 days .…”
Section: Discussionmentioning
confidence: 99%
“…associated with significant psychiatric side-effects, such as depression. 20 Previous studies showed that the median time required for the appearance or worsening of the depressive symptoms was 15 days. 21 In this study, however, during the 12-week therapy, minor depressive symptoms were found in 1 of the 10 patients with CHC and this patient did not manifest a worsening of depressive symptoms.…”
Section: Nterferon Therapy For Patients With Chc Ismentioning
confidence: 99%
“…The link between immune system, inflammation and depression was observed for the first time when IFN–α therapies, which activate inflammatory antiviral response, were introduced as a treatment for hepatitis C. Patients treated with interferon developed depression-like behaviors after 4 weeks of treatment initiationinitiation [ 92 ]. Patients with MDD have been observed to have higher levels of pro-inflammatory mediators such as IL–6, IL–12 and C–reactive protein compared to nondepressed individuals [ 93 , 94 ].…”
Section: Anti-inflammatory Activity Of Medicinal Mushrooms In Beating...mentioning
confidence: 99%